Lightning magnetic field measuring system in Bogota (2013)
This thesis presents the configuration and performance of a lightning radiated electromagnetic field measuring system in Bogotá Colombia. The system is composed by both magnetic and electric field measuring systems working as separated sensors. The aim of the thesis is the design and construction of a Magnetic Field Measuring System and the implementation of a whole lightning measuring system in Bogotá. The theoretical background, design process, construction and implementation of the system are presented and the analysis of signals obtained is discussed.